Contemporary debate on freedom of speech and expression concerning to film censorship laws in Malaysia - Islam, Md. Zahidul (CLJ Law, 2019)
Freedom of speech is a vital element to humanity and for the foundation of a free society. The making and exhibition of films also falls under the free speech clause. Alike to other fundamental liberties, freedom of speech doesn’t have any absolute form and it is related to the reputation of others like national security issues, public mental health and moral instincts. It is a contemporary debate that freedom of speech is restricted by the censorship laws. The aim of this paper is to identify the relationship between freedom of speech and expression concerning to censorship laws of Malaysia. It is a qualitative research. The information has been collected studying articles, books, newspapers and statutes. The restrictions on freedom of speech are acceptable for the interest of security of a state, public order and to establish friendly relationship with other foreign countries. In this case, censorship plays an important role to protect moral values and law of order situation in a country.